RECENT COLLECTION OF THE POISONOUS MUSHROOM, Clarkeinda trachodes (Berk.) FOR INDONESIA - Ivan Permana Putra; Oktan Dwi Nurhayat; Wahyu AJi Mahardika; Okta Yulia Sari (SEAMEO BIOTROP, 2024)
Clarkeinda trachodes is an interesting agaric and has been acknowledged as one of the poisonous mushrooms worldwide. This species has mentioned to be found in tropical regions of Asia, including Indonesia. However, no clear record has been found regarding the primary information and herbarium collection of this species in Indonesia. During our regular mushroom foraging at IPB University campus forest Indonesia, the basidiomata of Clarkeinda was encountered. The current study aimed to confirm the taxonomical position of our specimens based on morphological and molecular evidence. Fresh basidomata was observed on the macro- and micromorphological features. The molecular analysis and phylogenetic tree construction were done based on ITS 1/2 sequence. The combination of morphological and molecular evidence confirmed our specimen as C. trachodes. Morphologically, Clarkeinda trachodes BO24637 can be determined by a large basidiocarp of Agaricales, prominent pellicle on disc pileus, notable ring, reddish brown context and stipe when injured, and truncate apex of basidiospores. The BLAST result showed that our specimen has a high similarity to C. trachodes as the top hits. In addition, the phylogenetic tree constructed by ITS sequence committed specimen BO24637 as C. trachodes with 100% BS value. The current study resolves a clear and accessible document of C. trachodes in Indonesia. In addition, we provided the morphological and molecular information as well as herbarium collection of C. trachodes in Indonesia, which can be used for future study of this species.